A vallási entitások tipologizálása és alkalmazása a magyar helyzetre - Török Péter (2008)
More than half a dozen factors make the typologization of Hungarian religious entities difficult. The first, which is the characteristic of every typologization, is a certain level of arbitrariness, the second, is the diversity of these typologizations. The next problematic factor is that new religious movements (NRM) are sometimes treated separately and taken out of the traditional church-sect typology, and sometimes they are placed into one of the categories of the typology. Naturally, there are reasons for this separation, which are perhaps best summarized by Bryan Wilson (1993) in his historical comparative analysis. The consequence is that further typologies were created within NRMs. However, according to Wilson, these typologies were not based on ideal types, but only on a few typical characteristics (1993:70). These new categories either cannot be matched with to the previous ones even after a lengthy analysis, or can only be matched partially.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Filozófia, etika és vallástudományok